2019
DOI: 10.3390/lubricants7080065
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on the Tribological Performance of Titanium Alloys with Surface Modifications for Biomedical Applications

Abstract: The need for metallic biomaterials will always remain high with their growing demand in joint replacement in the aging population. This creates need for the market and researchers to focus on the development and advancement of the biometals. Desirable characteristics such as excellent biocompatibility, high strength, comparable elastic modulus with bones, good corrosion resistance, and high wear resistance are the significant issues to address for medical implants, particularly load-bearing orthopedic implants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 83 publications
1
27
0
Order By: Relevance
“…So, Results showed no toxic effect on the life cells. The samples were safe as known in previous work [23,24,25]. It is noticed that cells in the medium around the Ti foam samples are more than that on the surface of samples.…”
Section: Evaluation Of Toxicological and Cell Structure Adhesion By The In-vitro Methodsmentioning
confidence: 85%
“…So, Results showed no toxic effect on the life cells. The samples were safe as known in previous work [23,24,25]. It is noticed that cells in the medium around the Ti foam samples are more than that on the surface of samples.…”
Section: Evaluation Of Toxicological and Cell Structure Adhesion By The In-vitro Methodsmentioning
confidence: 85%
“…It was shown that cells growing on nitinol medical alloy and nanosized carbon coating have similar growth and development rates (Figure 8). Of course, nitinol is not the most modern and advanced medical alloy [36], but it is still widely used for the manufacture of implants.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased wear rate can be facilitated by large plastic deformation of the ductile matrix, whereas incorporating a harder reinforcing phase (h-BN) in the ductile matrix to some degree can lessen its ductility thereby reducing the propensity to wear easily [46,49]. The mechanism for improving the wear resistance properties of the composite can also be attributed to the inherent lubricating effect of the h-BN reinforcing phase on the worn surface, which in turn resulted in enhanced load bearing capacity of the surface and improved lubrication as wear proceeded [50][51].…”
Section: Densi Cation and Mechanical Behaviour Studiesmentioning
confidence: 99%